The Filter Bubble: Consumption Gen Z of Da’wah Content on YouTube - Irawan, Doni; Arenggoasih, Wuri (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Indonesia, as a multi-religious country with the largest number of Muslims in the world, is a country that adheres to a democratic system of government by always holding elections. However, issues and hoaxes about religion in election contestation are often raised as topics in political campaigns, especially through social media, which have the potential to trigger conflict. At the same time, the penetration of social media use by Gen Z as novice voters can be said to be relatively high. Today, the popularity of social media YouTube for Gen Z is a priority reference for accessing information related to religion. Ironically, this phenomenon indicates the existence of a filter bubble that limits the opportunities for Gen Z's exploration of religious issues. This picture encourages researchers to find out the existence of a bubble filter of da'wah content on social media consumption—YouTube on Gen Z. Using new media, bubble filters, and da'wah content as a theoretical framework, this research uses a case study research method involving 3 informants who are Gen Z with their respective religious interests and preferences. The findings of this study reveal that the existence of bubble filters as consumption of YouTube da'wah content on Gen Z is real. Gen Z has consumed da'wah content through YouTube for an average of 1-3 hours per day so that the content history appears homogeneous (homophily). YouTube as a crucial platform for users to enhance their religious awareness has been considered an important means for users to increase faith, expand knowledge, and gain inspiration, especially through da'wah content such as short studies, Prophet stories, and short lectures. However, the filter bubble phenomenon makes users only exposed to content that matches the interests and views of social media users, thus reducing the diversity of information received. Moreover, the bubble filter can narrow perspectives and create an isolated community, where users only interact with people who share similar views, limiting opportunities for dialogue with dissenting views.